인지적 동일시와 감정적 동일시의 상호작용 효과를 이용한 기부금 조성 전략 - 노정식(Noh, Jungsik); 조현진(Jo, Hyunjin) (대한경영학회지, 2009)
지금까지 많은 비영리조직들은 사람들에게 기부를 하도록 요청할 때, 동정심을 유도하거나 개인기부자들의 감정이입을 통해 기부를 받는 등 잠재기부자의 공감이라는 측면을 이용해서 간청을 해왔다. 그러나 개인적인 고통의 감정을 자극하는 간청 전략을 사용하는 것이 또한 효과적이라는 연구결과들이 보고되고 있다. 또한 대학에 기부한 경험이 있는 기부자들이 대부분 동문들이며, 동문들은 자신이 졸업한 모교와 동일시(Identification)하는 경향이 있다는 점에 착안하여, 기부동기 중 동일시의 동기를 바탕으로 동일시를 두 가지 차원인 인지적 동일시와 감정적 동일시로 구분하고 이들 두 차원 간 상호작용 효과를 검증하고자 한다. 따라서 본 연구에서는 인지적 동일시와 감정적 동일시를 자극하는 공감과 개인적 고통 차원의 간청 전략을 분석하고자 한다. 이러한 연구목적을 바탕으로, 본 연구는 국내 Y대학에 기부한 경험이 있는 사람들의 과거 기부 데이터(Objective Data)를 분석하였다. 그리고 이 데이터를 바탕으로 할당표본추출법을 사용하여 252명의 표본을 추출하고 설문조사를 실시하였다. 과거의 객관적 기부 데이터 및 설문조사를 통해 나온 결과를 바탕으로 구조방정식 모형분석을 한 결과, 감정적 공감 명분은 감정적 동일시에, 개인적 관계는 인지적 동일시에 정(+)의 영향을 주었다. 또한 인지적 동일시 및 감정적 동일시의 상호작용 효과가 있는 것으로 나타났다. 본 연구는 마케팅 영역에서 공감과 개인적 고통 정서라는 두 가지 상반된 측면의 간청전략을 분석하고 이들을 인지적 동일시, 감정적 동일시의 두 차원과 연관시켜 상호작용 효과를 분석하였다는 점에서 그 의미가 있다고 할 수 있다. This article finds that most donors who have the experience of donation are alumni and they tend to identify themselves with their alma maters. Thus, the aim of this study is to examine which solicitation strategy makes individual to identify oneself with the non-profit organization and finally lead to donate. Specifically, first, this study examines how the interaction of the cognitive identification and emotional identification affect giving behavior. Second, this study investigates methods of solicitation strategies that arouse donor to identify, and analyzes the difference between solicitation strategies based on empathy and personal distress. To reach these goals, this study used existing database of donors who donated to Y University, and next extracted samples of 252 people using quota sampling on the basis of this objective data, and then conducted a survey. Structural Equation Modeling on the basis of the results of existing objective donation data and survey were done to analyze. As a result, two among five hypotheses were rejected and the others were all supported. The results are as follows. First, as the effects of solicitation on identification, emotional empathy had positive effects on emotional identification, and personal relationship had positive effects on cognitive identification. Second, regarding the effects of identification on giving behavior, cognitive identification and emotional identification had no significant effect on donation sum, but the interaction of cognitive identification and emotional identification had positive effects on donation sum. The significance of this study is as follows. First, this study introduces solicitation variables that have rarely been studied in marketing and divides identification into two dimensions and analyzes their relative influences. Second, this study tries to maintain the rigor of the model by analyzing data collected from the survey together with donors’existing database. KCI Citation Count: 10